Digital Scavenger Hunt with LearningApps: A Strategy to Enhance Student Interest and Learning Outcomes in Islamic Religious Education - Muslikha, Al; Muhaemin; Muhammad Zuljalal Al Hamdany (Institut Agama Islam Negeri Kendari, 2026)
The low level of students’ interest and academic outcomes in the subject of Islamic Religious Education and Character Education highlights the need for more interactive learning innovations. This study aims to improve student engagement, interest, and academic outcomes through the implementation of a LearningApps-based Digital Scavenger Hunt. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles involving 27 students of Class IX.5 at SMPN 1 Bone-Bone, South Sulawesi, Indonesia. Data were collected through observation, learning interest questionnaires, and learning outcome tests, and were analyzed using descriptive quantitative methods. The results showed improvements in teacher and student activities, reaching the very good category in Cycle II. Students’ learning interest increased from 76.85% to 82.09%, while learning outcomes improved from an average score of 76.67 with 59.25% classical mastery to 85.55 with 92.59% classical mastery. These findings suggest that the implementation of a LearningApps-based Digital Scavenger Hunt contributed to improvements in students' engagement and academic outcomes. This study implies that Islamic Religious Education teachers can adopt gamification-based digital strategies, particularly for abstract topics such as the Hereafter, to foster active participation and deeper conceptual understanding. Furthermore, the findings offer practical guidance for integrating game-based learning platforms into character education curricula.